2015
DOI: 10.3390/nu7075259
|View full text |Cite
|
Sign up to set email alerts
|

High Vegetable Fats Intake Is Associated with High Resting Energy Expenditure in Vegetarians

Abstract: It has been demonstrated that a vegetarian diet may be effective in reducing body weight, however, the underlying mechanisms are not entirely clear. We investigated whether there is a difference in resting energy expenditure between 26 vegetarians and 26 non-vegetarians and the correlation between some nutritional factors and inflammatory markers with resting energy expenditure. In this cross-sectional study, vegetarians and non-vegetarians were matched by age, body mass index and gender. All underwent instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 44 publications
(53 reference statements)
1
35
2
1
Order By: Relevance
“…0 %, P = 0 . 58) Montalcini (2015) (30) Study Yu (2014) (37) Lee (2016) (20) 0 . 21 Fruits and vegetables are known as dietary sources of salicylic acid (62,63) , an active ingredient of anti-inflammatory medications (64) .…”
Section: Discussionmentioning
confidence: 99%
“…0 %, P = 0 . 58) Montalcini (2015) (30) Study Yu (2014) (37) Lee (2016) (20) 0 . 21 Fruits and vegetables are known as dietary sources of salicylic acid (62,63) , an active ingredient of anti-inflammatory medications (64) .…”
Section: Discussionmentioning
confidence: 99%
“…The average individual yearly weight gain is reduced when people limit consumption of animal foods [ 27 ]. Vegetarian diets seem to increase resting energy expenditure [ 28 ], which may be partly responsible for the lower BMI values in vegetarians.…”
Section: Plant-based Diets Body Weight and Metabolic Syndromementioning
confidence: 99%
“…It should be considered that these results refer predominantly to healthy Chinese subjects, and different results might be obtained for other ethnic groups or different states of health. For example, an association between blood pressure and REE has been reported in Nigerians and African Americans [ 45 ], higher fasting serum insulin is associated with increased REE in patients who are non-diabetic and have schizophrenia [ 21 ], hyperglycemia and glycemic intolerance were associated with an increase in REE in patients with type 2 diabetes [ 22 , 23 , 24 ], high vegetable fats intake is associated with high REE in vegetarians [ 26 ], and REE was increased by dietary protein during overfeeding [ 25 ]. The extant literature on the relationship among glycolipid metabolism, eating behaviors, and REE remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies in unhealthy populations have pointed out that higher fasting serum insulin was associated with increased REE in patients who are nondiabetic and have schizophrenia [ 21 ], and hyperglycemia and glycemic intolerance were associated with an increase in REE in patients with type 2 diabetes [ 22 , 23 , 24 ]. In addition, some recent studies showed that REE was increased by dietary protein during overfeeding [ 25 ], and high vegetable fats intake is associated with high REE in vegetarians [ 26 ]. Associations among glycolipid metabolism, eating behaviors, and REE have been reported in unhealthy subjects.…”
Section: Introductionmentioning
confidence: 99%